The effect of citric acid supplementation on growth performance, carcass weight, tibia bone breaking strength, and ash content of male ross 308 broiler chickens - Thokwane, Judith (My University, 2023)
Two experiments were conducted to determine the effect of citric acid inclusion level in the diet on growth performance, carcass weight, tibia bone breaking strength and ash content of male Ross 308 broiler chickens aged one to 35 days. The first experiment determined the effect of citric acid inclusion level in the diet on growth performance traits of male Ross 308 broiler chickens aged one to 21 days. The experiment commenced with 200 male day-old Ross 308 broiler chickens with an initial average live weight of 40±1.6g per chick. The chicks were assigned to five treatment groups in a completely randomized design, each replicated five times, and each replicate having ten chicks. The citric acid inclusion levels were at 0, 12.5, 25 or 50g per kg DM of feed. The second experiment determined the effect of citric acid inclusion level in the diet on growth performance, carcass weight, tibia bone breaking strength and ash content traits of male Ross 308 broiler chickens aged 22 to 35 days. The experiment commenced with 180 male Ross 308 broiler chickens aged 22 days. The chickens were assigned to four treatment groups, each having three replicate pens of eight chickens per replicate in a completely randomized design. Data was analysed using the General Linear model (GLM) procedures of the Statistical Analysis of System, version 9.3.1 software program. Where there were significant differences (P<0.05) between the treatment means, Tukey Multiple Comparison Test was used for mean separation. Citric acid inclusion in the starter diets improved (P<0.05) live weight and growth rate of male Ross 308 broiler chickens aged one to 21 days. Citric acid inclusion in the starter diets did not affect (P>0.05) daily feed intake, body weight gain and feed conversion ratio of male Ross 308 broiler chickens aged one to 21 days. The inclusion of citric acid did affect (P<0.05) live weight, body weight gain, feed conversion ratio and growth rate of chickens aged 22 to 35 days. Citric acid inclusion levels used in the present study influenced (P<0.05) DM and CP digestibility, ME intake and N-retention of male broiler chickens aged 22 to 35 days. The results of the current study showed that citric acid inclusion in a diet improved (P<0.05) chicken bone morphology. Thus, positive relationships were observed between citric acid inclusion level and right tibia bone weight, diameter, calcium, phosphorous and Magnesium contents of chicken bones aged 35 days. There were positive relationships between citric acid inclusion level and breast weight of male Ross 308 broiler chickens aged 35 days. Further studies are recommended to ascertain these findings.
Thesis (M.Sc. (Animal Production)) -- University of Limpopo, 2023
Keywords: Citric acid; Broiler chickens; Growth performance traits; Carcass weight; Bones; Dietary supplements; Bones -- Growth; Animal experimentation -- Effect of experimenters on; Tibia; Citric acid; Chickens as laboratory animals